PENERAPAN PERATURAN TATA TERTIB SEKOLAH DALAM MENAGGULANGI SISWA YANG MELANGGAR ATURAN DI SMA NEGERI 8 PONTIANAK - Yuni Widyaningsih; Supriadi Supriadi; Izhar Salim (Universitas Tanjungpura, 2019)
Abstract: The purpose of this research is to Entitled Application of School Rules and Regulations in Dealing with Students Who Break Rules in SMA Negeri 8 Pontianak. The problem in this study is